Applicability of ISCHEMIA to the daily practice of a Swiss University Hospital. (25th November 2020) - Meier, D; Mahendiran, T; Muller, O; Fournier, S
Abstract: Introduction: The ISCHEMIA trial found that an invasive strategy was not associated with a reduction in major adverse cardiovascular events when compared with optimal medical treatment (OMT) alone among patients with moderate/severe ischemia. However, given the extensive exclusion criteria of the study, we sought to investigate if these results would actually change our daily practice. Methods: We performed a retrospective analysis of the last 1, 000 consecutive PCIs undertaken in our university hospital in Switzerland. We applied the ISCHEMIA exclusion criteria to this population in order to estimate the proportion of patients that would have been excluded from the trial. Results: Between October 2018 and November 2019, 1, 000 PCIs were performed in a population with a mean age of 65.5 (IQR 51.0–76.0) years, of which 76.8% were men. Among these procedures, 603 (60.3%) were performed for an acute coronary syndrome (ACS) and 197 (19.7%) in the context of either an ACS within 2 months (n=131), or a PCI/CABG within 12 months (n=66) (Figure 1). A further 84 (8.4%) procedures were performed in patients with other high-risk features (ventricular arrhythmias, cardiac arrest, NYHA III-IV, eGFR <30 ml/min or LVEF <35%). Finally, 25 (2.5%) were performed in patients with unacceptable angina whilst on OMT, a cardiac transplant, a recent stroke, or another exclusion criterion. This left only 91 patients (9.1%) without any ISCHEMIA exclusion criteria. When considering only patients with SCAD (n=320), 229 (71.6%) would have been excluded due to the presence of at least one exclusion criterion. Conclusion: In this retrospective analysis of 1, 000 consecutive PCIs, the vast majority were performed in patients with at least one ISCHEMIA exclusion criterion. These results suggest that the impact of ISCHEMIA on the real-world practice of a medium-sized PCI center like ours is likely to be limited. Funding Acknowledgement: Type of funding source: None